Exploring urban-rural inequalities of maternal healthcare utilization in Bangladesh - A.T.M. Shariful Alam; Shorful Alam; Kashfia Mobasshira; S.M. Nuruzzaman Anik; Mohammad Nayeem Hasan; Muhammad Abdul Baker Chowdhury; Md Jamal Uddin (Heliyon)
Background: Bangladesh has made significant progress across various sectors, including healthcare. However, noticeable disparities persist in the healthcare sector, particularly in maternal healthcare between urban and rural areas. Despite substantial advancements in maternal healthcare services (MHCS), such as Antenatal care (ANC), Facility-Based Delivery (FBD), and Skilled Birth Attendants (SBA), utilization depends on various socioeconomic factors. This study aims to assess the impact of different factors and describe the urban-rural inequalities in maternal healthcare service utilization. Methods & study design: This study's analysis is based on data extracted from the 2017-18 Bangladesh Demographic and Health Survey (BDHS), following STROBE guidelines. Descriptive statistics provide an overview of the factors, and multiple logistic regression analysis identifies important factors in MHCS. Additionally, the Wagstaff decomposition method measures the concentration index, elasticity, contribution, and percentage contributions of different factors. Results: According to -BDHS 2017–18, this study found a 51.84 % utilization of ANC visits. Women with ''Higher Education'' had odds ratios of 3.04, 3.05, and 3.12 for ANC, FBD, and SBA, respectively, compared to the ''No Education'' group. Similarly, women with partners having ''Higher Education'' exhibited odds ratios of 3.04, 3.05, and 3.12 for ANC, FBD, and SBA, respectively. Rich families had odds ratios of 1.91, 2.42, and 2.5 compared to the ''poor'' group for ANC, FBD, and SBA, respectively. Mother's education contributed 28.62 %, 30.3 %, and 30.47 % for ANC, FBD, and SBA, respectively. The household wealth index contributed 26.16 %, 38.49 %, and 40.3 % for ANC, FBD, and SBA, respectively of the urban-rural difference. Conclusion: Maternal healthcare services utilization shows a significant disparity, with rural areas reporting much lower rates compared to urban areas. To achieve the Sustainable Development Goal (SDG), this study's findings can help policymakers ensure equitable access to quality care for all women, irrespective of their socioeconomic background or geographical location.